RFID-Based Tracking System For Real-Time Monitoring Of Students And Professors - Shruti Saxena; Shivani Saxena; Parth Chauhan (Educational Administration: Theory and Practice, 2024)
Managing the complex dynamics of a college campus requires an innovative and efficient tracking system for students and professors. Existing methods often fall short of delivering accurate real-time monitoring, leading to logistical challenges and communication gaps. In this research paper, we present a visionary solution—a futuristic RFID-based tracking system that revolutionizes campus management. By seamlessly integrating cuttingedge technologies, this system addresses the limitations of traditional methods and offers a transformative approach. Our proposed methodology centers on RFID tags, which act as digital fingerprints for individuals. These tags capture real-time location data, unlocking a treasure trove of insights. Leveraging advanced algorithms and data processing techniques, the system stores and analyzes this information in a centralized file, creating a comprehensive and dynamic view of the campus. Results from our initial trials showcase the system’s remarkable accuracy and reliability. Real-time tracking enables precise monitoring of student and professor movements, facilitating timely interventions and efficient resource allocation. Moreover, a user-friendly search functionality empowers students and professors to effortlessly locate individuals based on their names, fostering seamless communication and collaboration. This holistic approach to campus management holds tremendous potential for improving operational efficiency, communication, and overall campus experience.